Associations between serum levels of inflammatory markers and change in knee pain over 5 years in older adults: a prospective cohort study. Issue 4 (12th May 2012) - Stannus, Oliver P; Jones, Graeme; Blizzard, Leigh; Cicuttini, Flavia M; Ding, Changhai
Abstract : Objective: To determine the association between inflammatory markers and change in knee pain over 5 years. Methods: A total of 149 randomly selected subjects (mean 63 years, range 52–78; 46% female) was studied. Serum levels of high sensitivity C-reactive protein (hs-CRP), tumour necrosis factor alpha (TNF–α) and interleukin (IL)-6 were measured at baseline and 2.7 years later. Knee pain was recorded using the Western Ontario and McMasters osteoarthritis index questionnaire at baseline and 5 years later. Knee radiographic osteoarthritis of both knees was assessed at baseline, and knee bone marrow lesions, joint effusion and cartilage defects were determined using T1 or T2-weighted fat saturated MRI. Results: After adjustment for confounding variables, baseline hs-CRP was positively associated with change in total knee pain (β=0.33 per mg/l, p=0.032), as well as change in the pain at night in bed (β=0.12 per ml/pg, p=0.010) and while sitting/lying (β=0.12 per ml/pg, p=0.002). Change in hs-CRP was also associated with change in knee pain at night and when sitting/lying (both p<0.05). Baseline TNFα and IL-6 were associated with change in pain while standing (β=0.06 per ml/pg, p=0.033; β=0.16 per ml/pg, p=0.035, respectively), and change in TNFα was positively associated with change in total knee pain (β=0.66 ml/pg, p=0.020) and change in pain while standing (β=0.26 ml/pg, p=0.002). Adjustment for radiographic osteoarthritis or MRI-detected structural abnormalities led to no or minor attenuation of these associations. Conclusion: Systemic inflammation is an independent predictor of worsening knee pain over 5 years.